(untitled) (Revista Inclusiones, 2019)
The urgency of the study is predetermined by qualitative shifts in the information environment of the modern society, when the most important processes of the social and political life become mediated and are actively moving into the media environment. The interrelations of politics and journalism caused their integration in the political field of journalism. The new phenomenon has not been properly studied. There are no research instruments that are in line with its nature. In the article the fundamentals to develop a methodology for analyzing the political field of journalism have been considered.